PREVALENCE OF GUSTATORY AND OLFACTORY IMPAIRMENT IN DIFFERENT STAGES OF SARS-COV-2 INFECTED PATEINTS IN ISOLATION WARD - Shar, Mor Khan; Pirwani, Faheem Ahmed; Rana, Zahoor Ahmed; Mirza, Hamza Hassan; Rush, Ahsan Ullah; Jalbani, Bashir Ahmed (Journal of Ayub Medical College Abbottabad, 2022)
Background: To evaluate the prevalence of gustatory and olfactory impairment and its correlation with the severity of SARS-Cov-2 infection as per WHO guidelines. Methods: A total of 241 patients of both gender having age from 15-80 years were included in the study. It was cross Sectional study conducted at SARS-COV-2 Isolation wards of Pakistan institute of medical science Islamabad from 15thSeptember 2020 to 15th January 2021. Convenient sampling technique was used to collect data. A proforma was designed for this purpose. Participants were divided into 3 groups on the basis of age. Group-1 (15-30 years), group-2 (31-50 years) and group 3 (51-80 years). Further the participants were graded into mild, moderate and severe stages of Sars-Cov-2 infection according to WHO guidelines. Statistical analysis was performed by using SPSS version 20. Results: In this study 66% were male and 34% population were the female. Regarding the age groups 72% population were from the group-3. Results of study shows 47% in mild stage, 45% in moderate stage and 8% severe stage. The results regarding the Gustatory and Olfactory impairment showed that 126 had gustatory impairment while 130 patients had olfactory impairment. Conclusion: We found strong relationship of olfactory and gustatory changes associated with SARS-COV-2 patients. It is premature to conclude that taste and smell changes are strongly linked to SARS-COV-2 diagnosis. Further multi center researches are required to find out possible pathophysiological mechanism